Microstructured Polymer System Containing Proanthocyanidin-Enriched Extract from Limonium brasiliense as a Prophylaxis Strategy to Prevent Recurrence of Porphyromonas gingivalis - Pilatti, Fernanda; Isolani, Raquel; Valone, Larissa; de Paula, Mariana Nascimento; Caleare, Angelo de Oliveira; Ferreira, Sabrina Barbosa de Souza; Bruschi, Marcos Luciano; de Medeiros Araújo, Daniela Cristina; Guedes, Terezinha Aparecida; Hensel, Andreas; de Mello, João Carlos Palazzo (Planta Medica, 2022)
Periodontal diseases are a global oral health problem affecting almost 10% of the global population. Porphyromonas gingivalis is one of the main bacteria involved in the initiation and progression of inflammatory processes as a result of the action of the cysteine proteases lysin- and arginine-gingipain. Surelease/polycarbophil microparticles containing a lyophilized proanthocyanidin-enriched fraction from the rhizomes of Limonium brasiliense, traditionally named “baicuru” (ethyl acetate fraction), were manufactured. The ethyl acetate fraction was characterized by UHPLC by the presence of samarangenins A and B (12.10 ± 0.07 and 21.05 ± 0.44%, respectively) and epigallocatechin-3-O-gallate (13.44 ± 0.27%). Physiochemical aspects of Surelease/polycarbophil microparticles were characterized concerning particle size, zeta potential, entrapment efficiency, ethyl acetate fraction release, and mucoadhesion. Additionally, the presence of the ethyl acetate fraction-loaded microparticles was performed concerning potential influence on viability of human buccal KB cells, P. gingivalis adhesion to KB cells, gingipain activity, and P. gingivalis biofilm formation. In general, all Surelease/polycarbophil microparticles tested showed strong adhesion to porcine cheek mucosa (93.1 ± 4.2% in a 30-min test), associated with a prolonged release of the ethyl acetate fraction (up to 16.5 ± 0.8% in 24 h). Preincubation of KB cells with Surelease/polycarbophil microparticles (25 µg/mL) resulted in an up to 93 ± 2% reduced infection rate by P. gingivalis. Decreased activity of the P. gingivalis-specific virulence factors lysin- and arginine-gingipain proteases by Surelease/polycarbophil microparticles was confirmed. Surelease/polycarbophil microparticles decreased biofilm formation of P. gingivalis (97 ± 2% at 60 µg/mL). Results from this study prove the promising activity of Surelease/polycarbophil microparticles containing ethyl acetate fraction microparticles as a prophylaxis strategy to prevent the recurrence of P. gingivalis.
Keywords: Limonium brasiliense; Plumbaginaceae; adhesion; gingipain; microparticles; Porphyromonas gingivalis